Virtual screening of biologically active substances among S-containing derivatives of pteridine - Lohvinenko, N. V.; Shvets, V. M.; Dobrodub, I. V.; Швець, Володимир Миколайович (My University, 2024)
The aim of the work is to develop new bioregulators based on S-containing 6-R1-7-R2-2-R3-thioxo-2,3-dihydro-4(1H)-pteridine-ones using chemometric methods.
Keywords: тези доповідей